Investigating the influence of rainfall on soil carbon quantity in a tropical peatland - Richard, Adesiji Adeolu; Mohammed, Thamer Ahmed; Nik Daud, Nik Norsyahariati; Mustapha, Sa'ari; Sayok, Alexander Kiew; Padfield, Roryd; Evers, Stephanie (Elsevier, 2015)
Conversion of peat swamp forests to oil palm plantations has been a common practice in Southeast Asia in the face of oil palm boom. Soil carbon has been one of the numerous nutrients that are lost as a result of this practice. This work therefore attempts to study the influence of rainfall as one of the drivers of carbon loss in the peatlands. Four different sites were selected for the study which considered both dry and wet seasons. The results from the two seasons were analyzed and it was observed that soil carbon during the dry season was lower compared to the wet season’s.